Online Abuse : A Systematic Literature Review and Future Agenda - Kumar, Sarika (International Journal of Conflict Management, 2024)
Purpose The study aims to examine the conceptualization of online abuse (OA) and identifies theories, countries of research, top-cited articles, methodologies, antecedents, mediators, outcomes and moderators of OA and future research opportunities. Two research questions are addressed. How have the past studies on OA progressed regarding theories, context, characteristics and methodology? What future research opportunities can be done in this area? Design/methodology/approach This study systematically reviews, synthesizes and integrates OA literature using the well-recommended preferred reporting items for systematic reviews and meta-analyses (PRISMA) rules. The literature on OA was synthesized based on the Theory–Context–Characteristics–Methodologies (TCCM) framework given by Paul and Rosado-Serrano. Findings Through an examination of TCCM used in OA research, the review presents an all-inclusive and up-to-date overview of the research in this arena and sets a future research agenda to spur scholarly research. This systematic literature review has analyzed top-quality sample papers, published in the past decade. As a result, it contributes to a better understanding of this relationship by analyzing the different types of use and the value added to the shopping experience. Originality/value This study provides groundwork for researchers and promotes a deeper understanding of OA.
ISME